Assessment for Inclusion in Higher Education : Promoting Equity and Social Justice in Assessment. - Ajjawi, Rola.; Tai, Joanna; Boud, David; Jorre de St Jorre, Trina (Milton : Taylor & Francis Group, 2022)
Bringing together international authors to examine how diversity and inclusion impact assessment in higher education, this book provides educators with the knowledge and understanding required to transform practices so that they are more equitable and inclusive of diverse learners.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books